Metodologi hadis dalam karya al-Bayan pada Tawil ayat-ayat al-Quran karangan Abdul Aziz Salam - Abdullah Wahyu Hidayat, Mohd Zarif Muhammad Mustaqim, Ramle Mohamad Rozaimi, (Universiti Pendidikan Sultan Idris, 2017)
Metodologi hadis dalam karya al-Bayan pada Tawil ayat-ayat al-Quran karangan Abdul Aziz Salam by Abdullah Wahyu Hidayat, Mohd Zarif Muhammad Mustaqim, Ramle Mohamad Rozaimi,